Mothers' work status and the relationship to the academic performance of their Grade VI children in A. Montes Elementary School. - Ingalla, Ma. Socorro Lorelei M. (1991.)
The study was conducted primarily to determine whether there is a significant relationship between mothers' work status and the academic performance of their Grade VI children in A. Montes 1 Elementary School. Specifically, it aims to discover if there is a significant relationship between mothers' work status and their involvement in their children's activities. Further, it aims to determine if there is a significant relationship between mothers' involvement in the academic activities of their children and the children's academic performance., The population included 239 Grade VI pupils in A. Montes 1 Elementary School. This was divided into 2 strata: those pupils with working mothers and those with non-working mothers. Stratified random sampling was used to to choose the sample size. This was composed of 50 working mothers and 50 non-working mothers. Data was gathered by using interview schedule. Frequency counts, percentage distribution and chi-square test were used in the analysis of data. The study revealed that there is no significant relationship between mothers' work status and the academic performance of their children. That is, the satisfactory or unsatisfactory academic performance of the children has no relationship with their mothers' work status. Although there were more non-working mothers who supervise their children while they study, assist in assignments and projects and monitor their children's academic progress, the study revealed that there was no significant relationship between mothers' work status and their involvement in the academic activities of their children. Finally, it was found out that there was no significant relationship between the mothers' involvement in their children's academic activities and the academic performance of the children. That is, the involvement of the respondents in their children's academic activities does not significantly affect the academic performance of their children.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Grade VI Children -- Montes I Elementary School